Helios defines T cells being driven to tolerance in the periphery and thymus. Issue 7 (5th June 2014) - Ross, Ellen M.; Bourges, Dorothée; Hogan, Thea V.; Gleeson, Paul A.; van Driel, Ian R.
<x xml:space="preserve">Abstract</x> The expression of the Ikaros transcription factor family member, Helios, has been shown to be associated with T‐cell tolerance in both the thymus and the periphery. To better understand the importance of Helios in tolerance pathways, we have examined the expression of Helios in TCR‐transgenic T cells specific for the gastric H+/K+ ATPase, the autoantigen target in autoimmune gastritis. Analysis of H+/K+ ATPase‐specific T cells in mice with different patterns of H+/K+ ATPase expression revealed that, in addition to the expression of Helios in CD4+Foxp3+ regulatory T (Treg) cells, Helios is expressed by a large proportion of CD4+Foxp3− T cells in both the thymus and the paragastric lymph node (PgLN), which drains the stomach. In the thymus, Helios was expressed by H+/K+ ATPase‐specific thymocytes that were undergoing negative selection. In the periphery, Helios was expressed in H+/K+ ATPase‐specific CD4+ T cells following H+/K+ ATPase presentation and was more highly expressed when T‐cell activation occurred in the absence of inflammation. Analysis of purified H+/K+ ATPase‐specific CD4+Foxp3−Helios+ T cells demonstrated that they were functionally anergic. These results demonstrate that Helios is expressed by thymic and peripheral T cells that are being driven to tolerance in response to a genuine autoantigen.